Risk factors for nonunion after intramedullary nailing of femoral shaft fractures: Remaining controversies. Issue 8 (August 2015) - Metsemakers, W.-J.; Roels, N.; Belmans, A.; Reynders, P.; Nijs, S.
Abstract Introduction Intramedullary nailing (IMN) is the preferred treatment for femoral shaft fractures in adults. Although previous studies published good outcomes, some controversies remain. The purpose of this retrospective study was to identify factors that influence outcome after IMN for femoral shaft fractures. Materials and methods Between July 1998 and July 2013, we treated 230 patients with 248 femoral shaft fractures. Statistical analyses were performed to determine predictors of nonunion. The following set of variables was selected based on the speculation that they would contribute to the outcome: sex (male or female), smoking, obesity, polytrauma, fracture type, open fractures, Gustilo type, primary external fixation (EF) and reaming. Results Initial fracture stabilization was performed by IMN in 161 (64.9%) and by EF in 87 (35.1%) fractures. There were no documented cases of deep infection. Nonunion was diagnosed in 27 patients with 28 fractures (11.3%). Factors affecting nonunion in the univariate analysis were Arbeitsgemeinschaft für Osteosynthesefragen/Orthopaedic Trauma Association (AO/OTA) fracture type (odds ratio [OR] 25.0; p < 0.0001), Gustilo type (OR 0.64; p = 0.0358), and EF (OR 0.42; p = 0.0401). Multiple logistic regression analysis only identified AO/OTA fracture type (OR 22.0; p < 0.0001) as a risk factor for nonunion. Fracture reaming did not change the outcome (OR 0.80; p = 0.6073). A separate analysis showed that damage control EF was not a risk factor in polytrauma patients (OR 0.76; p = 0.5825). Conclusions Fracture stabilisation with IMN is a good treatment option for femoral shaft fractures in adults. The purpose of this study was to evaluate risk factors of poor outcome after IMN of femoral shaft fractures. The present analysis revealed that there was no difference in the outcome whether the fracture was reamed or not. Univariate and multivariate analysis could only correlate AO/OTA fracture type with the occurrence of nonunion. Therefore, in this study, unreamed nailing and damage control EF were not associated with a negative outcome.